GROWTH AND PROPERTIES OF STACKED SELF-ASSEMBLED IN0.5GA0.5AS QUANTUM DOTS - Aryanto, Didik; Othaman, Zulkafli; Ismail, Abd. Khamim (Universitas Negeri Surabaya, 2012)
Self-assembled In0.5Ga0.5As quantum dots (QDs) were grown using metal-organic chemical vapor deposition (MOCVD) on GaAs (100) substrate with different number of stacking QDs layers. Surface study using atomic force microscopy (AFM) shows that surface morphology of the self-assembled QDs change with different number of stacking QDs layers caused by the previous QDs layers and the thickness of the GaAs spacer layers. PL measurement shows variation in the PL spectra as a function of number of stacking layers of In0.5Ga0.5As QDs. The PL peak positions blue-shifted from 1225 nm to 1095 nm and dramatically increase in intensity with increasing number of stacking QDs layers.